Phaeohyphomycosis of Lower Limb: A Rare Case Report - Chakma, Sushanta; Kolte, Sachin; Sharma, Preeti; Capoor, Malini R (Annals of Pathology and Laboratory Medicine, 2019)
Phaeohyphomycosis is a chronic, progressive cutaneous and subcutaneous infection caused by melanised or dermaticeous fungi and characterized by the presence of brown mycelial structures on fine needle aspiration cytology. These fungi are associated with rural population, involved in various agricultural and outdoor activities. The clinical manifestations that includes superficial and deep local infection to disseminated infection. Herein, we describe the clinical and fine-needle aspiration cytology features of a case of phaeohyphomycosis caused by Phialophora verrucosa.